A decrease in spontaneous activity in medial prefrontal cortex is associated with sustained hallucinations in chronic schizophrenia: An NIRS study - Yanagi, Masaya (Sci Rep, 2020)
In functional imaging, accumulating evidence suggests that spontaneous activity decreases during the resting state in the core brain regions of the default-mode network [e.g. medial prefrontal cortex (mPFC)] in schizophrenia. However, the significance of this decreased activity has not been clarified in relation to its clinical symptoms. In this study, near-infrared spectroscopy (NIRS), which is a simple imaging modality suitable for resting state paradigm, was used to evaluate the intensity of the spontaneous activity during the resting state in chronic schizophrenia. Consistent with previous findings of fMRI studies, spontaneous activity decreased in the mPFC of patients with schizophrenia. In addition, the decreased spontaneous activity was associated with severe hallucinations in this region where reality monitoring is fundamentally engaged. These results may encourage additional application of NIRS with the resting state paradigm into daily clinical settings for addressing the broad phenotypes and unstable course of schizophrenia.